Análise de fotocondução e efeito de memória resistiva em filmes finos de ZnO dopados com sódio - Magalhães, Bruno Trefilio (Universidade Federal de São Carlos, 2025)
With the increasing use of computational resources in everyday life, the continuous search for materials that can lead to advances in electronic devices and computing in general is necessary, whether in terms of computational or energy efficiency. In particular, zinc oxide (ZnO) presents favorable properties for applications in both photonics and the development of memristors. The investigation of the operating and performance characteristics of materials with memristive properties can improve the way we store information, and new computational architectures can be established, such as neuromorphic computing. In this work, the photoconduction characteristics and the memristive effect under the influence of ultraviolet light and different atmospheres on a thin film of 𝑍𝑛𝑂 doped with sodium (ZnO:Na) are investigated. The photoconductivity of the film was evaluated in several atmospheres - argon, synthetic air, free atmosphere, nitrogen, oxygen, carbon dioxide and vacuum - as well as the role of different light stimuli in photoconduction. In the absence of oxygen, the persistence of photoconductivity (PPC) phenomenon is observed more intensely in vacuum and carbon dioxide, with half-lives longer than one hour. The presence of oxygen is destructive to the conductivity of the film, impairing the retention of long-term memory (LTM). For the memristive effect, voltage versus current scans (I-V scans) were performed on the sample immersed in dry atmospheres (synthetic air and carbon dioxide) and in a free atmosphere. Lighting enhances the memristive effect, as seen in the larger internal areas when illuminated: 219𝜇A in synthetic air, 147𝜇A in a free atmosphere and 17𝜇A in carbon dioxide, compared to initial areas of around 0.1𝜇A. The memristive characteristics of the film are not altered by lighting but by the atmosphere, reinforcing that memristance is a surface effect.
Photoconduction and resistive memory effect analysis in sodium-doped ZnO thin films
Keywords: Fotocondutividade; Óxido de Zinco; Memristor; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::TRANSP.ELETRONICOS E PROP. ELETRICAS DE SUPERFICIES;INTERFACES E PELICULAS; ENGENHARIAS::ENGENHARIA ELETRICA::MEDIDAS ELETRICAS, MAGNETICAS E ELETRONICAS; INSTRUMENTACAO